Interparticle hydrogen bonding can elicit shear jamming in dense suspensions. Issue 11 (November 2018) - James, Nicole; Han, Endao; Cruz, Ricardo; Jureller, Justin; Jaeger, Heinrich
Abstract Dense suspensions of hard particles in a liquid can exhibit strikingly counter-intuitive behaviour, such as discontinuous shear thickening (DST)1–7 and reversible shear jamming (SJ) into a state where flow is arrested and the suspension is solid-like8–12 . A stress-activated crossover from hydrodynamic interactions to frictional particle contacts is key for these behaviours2–4, 6, 7, 9, 13 . However, in experiments, many suspensions show only DST, not SJ. Here we show that particle surface chemistry plays a central role in creating conditions that make SJ readily observable. We find the system's ability to form interparticle hydrogen bonds when sheared into contact elicits SJ. We demonstrate this with charge-stabilized polymer microspheres and non-spherical cornstarch particles, controlling hydrogen bond formation with solvents. The propensity for SJ is quantified by tensile tests12 and linked to an enhanced friction by atomic force microscopy. Our results extend the fundamental understanding of the SJ mechanism and open avenues for designing strongly non-Newtonian fluids. Dense suspensions of hard particles readily display discontinuous shear thickening under shear but not reversible shear jamming. Here it is shown that the formation of interparticle hydrogen bonds is crucial for the shear jamming of these suspensions.